Circadian changes in peripheral temperature and physiological responses under solar exposure and shed during summer in Karan Fries heifers - Singh, Raghuraj; Singh, S V (The Indian Journal of Animal Sciences, 2011)
Karan Fries heifers (8), 1.5-2.0 year-old, were divided into 2 groups (4 each). Group 1 was exposed to direct solar radiation during summer (Dbmin 18°C, Dbmax 40.2°C), whereas, group 2 was maintained under existed shed at NOR!, Kamal. The feeding consisted of green fodder and water was ud lib. The surface body temperature at different body sites, viz. fore head, ear, dewlap, flank, fore and hind leg (lower, middle and upper) was recorded by using non-contact temperature measurement instrument at 3 h intervals. The physiological parameters (RR, HR and RT) were also recorded at similar intervals. The difference between maximum and minimum peripheral skin temperature in groups I and :2 at forehead (14.54° and 7.01°C), ear (19.50° and 19.12°C), dewlap (16.34° and 7.59°C), flank (14.50° and 14.04°('), respectively, were higher than at different locations offore-and hind-legs. The surface temperature was higher in exposed group than protected at all the sites and surface temperature rises in relation to the length of radiation exposure. The increase in the respiratory frequency over their lowest values in the exposed group was about 4-time, whereas in protected group it was about 2-times and distress symptoms were not pronounced in protected group ofanimals. Therefore, crossbred heifers should be protected from extreme hot conditions and direct sun exposure be avoided.